Intrinsic and synaptic regulation of axonal excitability in dopaminergic neurons - Seddon, Jackie; Kramer, Paul F. (Frontiers in Cellular Neuroscience, 2025)
Dopamine released from the axon terminals of dopaminergic neurons is central to behaviors like reward learning and complex motor output. The dynamic control of dopamine release canonically occurs through two main mechanisms: the modulation of somatic excitability and the regulation of vesicular release at presynaptic boutons. However, there is also a third mechanism: the precise and local control of axonal excitability. Together, these three mechanisms control the amplitude and timing of dopamine release from terminal axons. In this review, we examine the intrinsic properties and dynamic modulation of dopaminergic axons. First, we will examine their intrinsic properties, including membrane biophysics and morphological features. Second, we will focus on the modulation of axonal excitability through receptor signaling. Finally, we will review how drugs of abuse directly influence axonal physiology, and how axonal excitability influences the progression and etiology of Parkinson’s disease. Through this review we hope to highlight the important role that modulation of axonal excitability plays in controlling dopamine release, beyond action potential propagation.